Hermeneutika Historis Humanistik Mohamed Talbi - Karim, Maulana Ikhsanun (MAGHZA, 2018)
This paper attempts to examine the thoughts of Mohamed Talbi on hermeneutics based on human history. The concept of humanistic historical hermeneutics is a solution breakthrough to understand a law that is considered to be contrary to the goal rather than the law itself, which is justice. Mohamed Talbi as one of the Muslim scientists in the field of history has provided this understanding of Islam. The thinker is not only in line with the times, but also can not be separated from the basic values taught in Islam itself such as justice, equality, and benefit. Its proven knowledge and clear methodology make us have nothing to lose if we learn the fruits of their thinkers work. Keywords: Mohamed Talbi, reading history, thoughts, methodology